2020
DOI: 10.1177/0021998320916231
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of the impact protection properties for Kevlar® fabrics under different orientation layers and non-Newtonian fluid compositions

Abstract: Use of colloidal silica suspensions impregnated in Kevlar® fabrics is new avant-garde of protection equipment for stab wounds and piercing objects. Kevlar® fabrics impregnated with non-Newtonian fluids have been used for protection against sharp blows, mainly due to their lightweight, good flexibility, and superior resistance properties. The aims of this investigation are to demonstrate that Kevlar® fabric impregnated with shear thickening fluids could be improved its performance through the use Aminopropyltri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The power-law index chosen is n1=0.9 and n2=1.1 respectively. In Figure 9A, we have a velocity profile near the exit for all three cases of stress cut-off 3.72 ×10 -6 Fu/lu 2 , 4.90 ×10 -6 Fu/lu 2 and 6.28 ×10 -6 Fu/lu 2 . The analytical velocity profile was obtained using the equation for 40 and 41, and simulations are compared in Figure 9A.…”
Section: Resultsmentioning
confidence: 99%
“…The power-law index chosen is n1=0.9 and n2=1.1 respectively. In Figure 9A, we have a velocity profile near the exit for all three cases of stress cut-off 3.72 ×10 -6 Fu/lu 2 , 4.90 ×10 -6 Fu/lu 2 and 6.28 ×10 -6 Fu/lu 2 . The analytical velocity profile was obtained using the equation for 40 and 41, and simulations are compared in Figure 9A.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors also studied the combination of these fluids with other materials to boost their protective properties. Santos et al proved that the addition of STF to Kevlar fabrics improves the performance of these substrates under impact tests [ 17 ]. Lu et al and Santos et al also demonstrated that the combination of STF with materials like wale-knitted spacer fabrics and Kevlar woven samples, respectively, can be applied as a material for personal protection [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The shear thickening fluid (STF) impregnated high tenacity fibre is found in soft body armour application. Shear thickening behaviour is reversible, which makes the STF-treated body armour flexible yet provides strength to it [1][2][3][4][5]. A concentrated nanosized silica particle dispersed in polyethene glycol (PEG) shows the behaviour of shear thickening fluid [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%